The breeding seabird community reveals that recent sea ice loss in the Pacific Arctic does not benefit piscivores and is detrimental to planktivores. (December 2020) - Will, Alexis; Takahashi, Akinori; Thiebot, Jean-Baptiste; Martinez, Akashia; Kitaiskaia, Evgenia; Britt, Lyle; Nichol, Dan; Murphy, James; Dimond, Andrew; Tsukamoto, Shota; Nishizawa, Bungo; Niizuma, Yasuaki; et al.
Abstract: Recent dramatic reductions of winter sea ice in the northern Bering Sea have raised the possibility that a rapid ecological transformation is underway. It has been hypothesized that with sufficient sea ice loss the cold pool thermal barrier separating the northern and southern Bering Sea would be breached, potentially benefiting piscivorous seabirds with an influx of abundant forage fish, but maybe causing food limitations for planktivorous seabirds that rely on cold-water associated species of zooplankton. During 2016–2019, we examined responses of the seabird community breeding on St. Lawrence Island to variable winter sea ice extent (low in 2018–2019). The seabird community includes piscivorous black-legged kittiwakes, thick-billed and common murres, and planktivorous crested and least auklets. We used a combination of stable isotope analysis and nutritional stress status analyses to examine if the region's ecosystem has shifted to a pelagic prey base, and whether either foraging guild benefitted from such a shift. To interpret bird responses, we used stable isotope analyses of prey and trawl survey-derived abundance of forage size fish. Stable isotope values in blood tissues revealed no change in the prey base as reflected in the isotopic space used by the seabird community across the four study years. Sea-ice loss was, however, associated with increased nutritional stress in all seabird species and diverging foraging niches within guilds. Benthic forage-sized fish remained a key food source, with their abundance stable since 2010, and benthic-foraging thick-billed murres experienced relatively low nutritional stress across the study period. A significant increase in common murre nutritional stress levels between 2016 and 2017, and a shift in their isotopic niche indicative of higher reliance on benthic prey coincided with a decline in the abundance of pelagic forage fish in the region. Surface-foraging black-legged kittiwakes experienced steady increases in nutritional stress as the abundance of pelagic forage fish declined. The spring sea-ice loss was detrimental to planktivorous least and crested auklets that rely on zooplankton advected from the Bering Sea basin. During the study period both auklets have experienced severe nutritional stress (2018) and colony-wide reproductive failures (2018 and 2019). In conclusion, we found that increasingly warm conditions during 2016–2019 have challenged the adaptive ability of seabirds relying on pelagic fish and zooplankton advected into the region each summer, but have not yet resulted in a reorganization of the northern Bering Sea's benthic-dominated ecosystem.